Menurunkan Cacat Crawling pada Keramik Berglasir Putih dengan Metode Six Sigma di PT HSI - Hadi Suprapto (Teknik Industri Universitas Indraprasta PGRI, 2019)
In the current of globalization, the development of industry in the word both in manufacturing and servis sector has undergone change and development. Each company and competed to win the competition and market share. In achieving it’s vision and mision, the company continues to servucess improve theproduction and quality managenement controlling and improving the quality to word the target 3,4 failures per million opportinities (DPMO) for each transaction of good and services. Six Sigma is a method or thechnique of controlling and dramatic quality improvement is a new breaktrough in the fieldof quality management. By using the Six Sigma method, it can be seen that the quality of white glazed ceramics produced by PT HSI in 2017 was at the level of 2.35 Sigma with a defect rate of 198345 for a million production (DPMO). Through the DMAIC method, the value of Six Sigma increased to 2.55 Sigma with a damage rate of 147749 defects for a million production. Through the Six Sigma approach in this study crawling defects can be improved from 7.30% to 3.55%.Keyword: Quality, Ceramic, Six Sigma, DMAIC, and Crawling